Pemikiran Hasan Hanafi Tentang Teologi Islam - Musbih, Musbih; Andaryuni, Lilik (Sekolah Tinggi Agama Islam Al-Furqan, Makassar - Indonesia, 2025)
This study explores the thought of Hasan Hanafi within the framework of social reconstruction in response to the Industrial Revolution from the perspective of Islamic theology. The central focus is on how Hanafi, as a prominent figure in contemporary Islamic intellectual reform, offers a significant contribution in shifting Islamic theology from a theocentric and abstract orientation to a praxis-based, transformative, and socially grounded discourse.. This concept urges Muslims to contextualize religious teachings to address social, political, and economic challenges in a tangible manner. Hanafi employs a critical hermeneutic approach, particularly in reinterpreting religious texts from an anthropocentric perspective that centers on human beings and their social realities. This research adopts a qualitative methodology through library research, relying on secondary sources such as books, journals, and Hanafi’s own works. The study aims to demonstrate how Hasan Hanafi’s ideas can serve as a foundation for social reconstruction in addressing the challenges posed by the Industrial Revolution within Islamic theological discourse. This research contributes to Islamic studies by highlighting the relevance of Hasan Hanafi’s anthropocentric and liberation-oriented theology in constructing a socially engaged theological response to contemporary global transformations, particularly those brought about by industrial and technological revolutions.